Tumor responsiveness to statins requires overexpression of the ARF6 pathway. (3rd July 2016) - Sabe, Hisataka; Hashimoto, Ari; Hashimoto, Shigeru; Oikawa, Tsukasa
ABSTRACT: The mevalonate pathway results in the prenylation of small GTPases, which are pivotal for oncogenesis and cancer malignancies. However, inhibitors of this pathway, such as statins, have not necessarily produced favorable results in clinical trials. We recently identified properties of statin responders, together with the underlying molecular mechanisms and simple biomarkers to predict these responders.